Measurement of self control among university Students (Journal of the College of Education for Women, 2019)
Self control is the perception of the individual of his duty at, the capacity of self testing in systematic durations and the ability of individuate to control his behavior, The control will be spontaneous when the individual will have a special ideas about the correct or incorrect behavior and choosing his way according it.The present study airs at:1- building and measuring self control and balancing among means among university students according to gender and specialization.To achieve the above mention aim, the two researchers built a scale of self control depending on some theories and applying it on a sample consists of (400) male and female students in Baghdad university studying in scientific and human fields. The two researchers make the necessary procedures such as reliability and constancy reaching to discriminative power by the two extreme groups style, relation of item with total scone of scale and factorial analysis of self control scale and applying on a sample consists of (495) students for measuring purpose. When data had been collected and processed statistically, the researchers concludes the following results:University students have the capacity of controlling their behavior through self monitoring , hedging it and responding to the different doily life situations such as cognitive, academic, social and emotional ones and there is no difference in controlling self among university students according to gender and specializing.